Plate fixation in periprosthetic femur fractures Vancouver type B1—Trochanteric hook plate or subtrochanterical bicortical locking?. Issue 12 (December 2016) - Lenz, Mark; Stoffel, Karl; Kielstein, Heike; Mayo, Keith; Hofmann, Gunther O.; Gueorguiev, Boyko
Abstract: Introduction: Proximal plate fixation in periprosthetic femur fractures can be improved by plate anchorage in the greater trochanter (lateral tension band principle) or bicortical locking screw placement beside the prosthesis stem in an embracement configuration. Both concepts were compared in a biomechanical test using a femoral hook plate (hook) or a locking attachment plate (LAP). Methods: After bone mineral density (BMD) measurement in the greater trochanter, six pairs of fresh frozen human femora were assigned to two groups and instrumented with cemented hip endoprostheses. A transverse osteotomy was set distal to the tip of the prosthesis, simulating a Vancouver B1 fracture. Each pair was instrumented using a plate tensioner with either hook or LAP construct. Cyclic testing (2 Hz) with physiologic profile and monotonically increasing load was performed until catastrophic failure. Plate stiffness was compared in a four-point-bending-test. Paired student's- t -test was used for statistical evaluation (p < 0.05). Results: Mean BMD was 250 mgHA/ccm ± 47. The hook construct exhibited a significantly (p = 0.015) lower number of cycles and load to failure (26′177 cycles ± 2777; 3′118N ± 778) correlating significantly with BMD ( R 2  = 0.83; p = 0.04) compared to the LAP construct (37′423 cycles ± 5′299; 4′242N ± 1′030) ( R 2  = 0.71;p = 0.11). BMD was a significant covariate (p = 0.01). Plate stiffness was in a comparable range (hook Plate 468 N/mm ± 7; LCP 445 N/mm ± 6). Conclusion: Subtrochanterically placed LAP provides an increased fixation strength under repetitive loading compared to hook plate fixation in the greater trochanter. Trochanteric fixation is highly BMD dependent and may be restricted to major greater trochanteric involvement requiring stabilization.